O ensino da linguagem escrita na pré-escola: uma análise à luz da Pedagogia Histórico-Crítica e da Psicologia Histórico-Cultural - NASCIMENTO, Sandra Aparecida Tavares Barbosa do (2023)
This dissertation is linked to the line of research “Public Policies in Education, Training Processes and Diversity”, from the graduation program in Education (PPGE) of UNOESTE, Presidente Prudente Campus, and aims to understand the historical-critical pedagogy and historical-cultural psychology, the conceptions and practices for teaching written language in preschool, the last two years of early childhood education in a public school in a medium-sized city in the countryside of São Paulo. These presented theories contributions that are considered essential to the research when discussing the psychic development linked to the objective conditions of life and education. In order to carry out the research, it was used a systematic literature review from 2018 to 2022, and we chose as databases the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (Capes); Scientific Electronic Library Online – Scielo and the Brazilian Digital Library of Theses and Dissertations (BDTD). The analyses of the articles, dissertations and theses pointed out the need for further research, highlighted the importance of written language for the development of babies and children and the variety of subjects and approaches that coincide with this process. It was also used semi-structured interviews with ten teachers. Through the method of historical-dialectical materialism, it had been undertaken the analyzes based on two analytical categories, namely: a) written language: conceptions and practices; and b) psychology of guiding documents and didactic resources in teaching practice. We concluded that the participants understand writing as a broader content than just the writing technique and literacy, itself, as a goal of elementary school. However, it is necessary to deepen discussions about the non-naturalization of human development, in order not to understand it as a domain of previously given powers. In this sense, it was pointed out fundamental issues to be deepened in in-service training, such as the periodization of psychic development; the prehistory of writing, notably the playing of social roles; the contents of operational training and theoretical training; relations between the teaching of written language and the teaching of the writing system; relationship between oral language and written language and also phonological awareness, in particular, phonemic awareness through sound analysis of the word. It is possible to highlight the importance of the cities having their own curriculum, elaborated collectively. This work emphasizes the need for careful analysis of documents and teaching materials originating from federal or state programs, so that appropriation by overcoming, if necessary, is carried out, a fundamental issue for a teaching network that intends to advance collectively to achieve the maximum development of babies and children. The appropriation of written language will be fully realized in elementary school, however, early childhood education must invest in creating the basis for this appropriation.